2017
DOI: 10.1063/1.4997887
|View full text |Cite
|
Sign up to set email alerts
|

A novel in situ electrochemical NMR cell with a palisade gold film electrode

Abstract: In situ electrochemical nuclear magnetic resonance (EC-NMR) has attracted considerable attention because of its ability to directly observe real-time electrochemical processes. Therefore, minimizing the incompatibility between the electrochemical device and NMR detection has become an important challenge. A circular thin metal film deposited on the outer surface of a glass tube with a thickness considerably less than the metal skin depth is considered to be the ideal working electrode. In this study, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…As expected from the analytical expressions given by Chen et al, 23 the thickest planar disk electrode showed the worst performance in terms of mass sensitivity -S rel = 86.4%. For all other structures except for the narrow channel sidewall configuration, the penalty to be paid in comparison with the electrode-free configuration, in terms of mass sensitivity, was <5%.…”
Section: Performance Analysis Of Simulated Electrode Topologiessupporting
confidence: 71%
See 2 more Smart Citations
“…As expected from the analytical expressions given by Chen et al, 23 the thickest planar disk electrode showed the worst performance in terms of mass sensitivity -S rel = 86.4%. For all other structures except for the narrow channel sidewall configuration, the penalty to be paid in comparison with the electrode-free configuration, in terms of mass sensitivity, was <5%.…”
Section: Performance Analysis Of Simulated Electrode Topologiessupporting
confidence: 71%
“…The challenge of introducing conductive structures for in situ electrochemical analyses with high-field NMR is reflected by there being only a few reports available. [38][39][40][41][42][43] Microfabrication introduces new opportunities. On one hand, ultra-thin metallic layers, which are NMR transparent, can be achieved by rather standard MEMS techniques.…”
Section: Fabrication Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the RF field homogeneity in the volume of substances, we presented an original EC-qNMR cell with palisade structure of working electrode that was suited for routine operations in a modern high-frequency NMR spectrometer [ 23 ], as shown in Figure 1 . The homemade electrolytic cell was fabricated from several glass tubes with different outer diameters.…”
Section: Methodsmentioning
confidence: 99%
“…The reason why inductively coupled probes were chosen as a way to improve the performance of electrochemical reaction analysis by NMR is: first, because it is an approach that had not previously been tried for this application and; secondly, because most approaches to improve the quality of the coupling between electrochemistry and NMR focus on alterations to the electrochemical itself (3, 8-11, 14, 18, 69-84) and don't tend to focus on improvements to the NMR probe. Some solutions involve placing the electrodes outside the detection region (81)(82)(83)(84), using RF chokes (filters) (14,18,81,82), using nonmetallic electrodes such as carbon microfibers (81)(82)(83) or even metallic thin-films (11,70,71).…”
Section: Inductively Coupled Probesmentioning
confidence: 99%